Application of Mobile Tourism for Kedah - Alkhazali, Abdel Rahman Mohammad (2012)
Tourism sector is one of the most important economic sectors in hIalaysia and it attracts large numbers of tourists around the world. Tourists face problem of helping access in some remote area in Malaysia. However, Mobile coverage in Malaysia is very help and extensive. This study proposes a mobile application for tourism to serve tourist in Kedah. This study will contribute to support this sector, so this application will provide information, pictures and videos of tourist attractions in Malaysia in state of Kedah, that help the tourists to retrieve information in places that lacks Internet. In addition, this study has use the (Vaishnavi & Kuechler) methodology to develop application. Furthermore, this application will be built on the basis of advanced search to achieve the speed and ease of use, such as coding to filter and count the words.